IMPLEMENTASI STRATEGI PEMASARAN DIGITAL PADA by.U SEBAGAI PROVIDER DIGITAL BAGI GENERASI Z - Krisna Putra Hermansyah; Lia Nirawati (Cahaya Ilmu Bangsa, 2025)
Among the many benefits of digital marketing are its global reach, lower costs, and real-time measurement of campaign effectiveness. With the right digital marketing approach, by.U was able to attract Generation Z, who grew up in the digital age and largely rely on social media to discover new items. One of the tactics used by.U is content marketing, where they use platforms such as Instagram and TikTok to create interesting and relevant material to increase brand exposure and traffic. In addition, by.U uses influencer marketing by collaborating with influencers such as Isyana Sarasvati to influence the shopping habits of generation Z through strategies that are lighthearted and consistent with their brand identity. Finally, social media marketing is used to sell products and establish relationships with customers by using clear language and staying in touch with the audience. With an emphasis on engaging content, working with influencers, and active participation on social media, U effectively executes an efficient digital marketing plan to connect with and appeal to generation Z.